Supramolecular hydrogels based on cellulose for sustained release of therapeutic substances with antimicrobial and wound healing properties - Forero-Doria, Oscar; Polo, Efrain; Marican, Adolfo; Guzmán, Luis; Venegas, Bernardo; Vijayakumar, Sekar; Wehinger, Sergio; Guerrero, Marcelo; Gallego, Jaime; Durán-Lara, Esteban F. (Carbohydrate polymers, 2020)
•A cellulose-chalcone hydrogel containing carbon nanotubes was successfully developed.•The hydrogel was characterized by swelling tests, FT-IR spectroscopy, thermogravimetric analysis and SEM.•The hydrogel allows the sustained release of simultaneous therapeutic substances.•Linezolid is more effective when it is sustained-released from the hydrogel. A multifaceted hydrogel-based formulation was reported. The hydrogel was prepared by crosslinking cellulose and substituted chalcone. Moreover, the formulation was conjugated with carbon nanotubes with the aim of increasing the loading amount of bioactive compounds such as allantoin, dexpanthenol, resveratrol and linezolid. The hydrogel formation was confirmed by swelling tests, FT-IR spectroscopy, thermogravimetric analysis and SEM. The hydrogel showed an improved release rate of therapeutic substances, exhibiting a simultaneous and coordinated release according to the chromatographic studies. The efficacy of drug release was confirmed by wound closure and in vivo wound healing studies that showed promising healing results. The antibacterial assays demonstrated that the sustained release of linezolid tends to be very effective. In conclusion, a multifaceted formulation based on carbon nanotube-containing cellulose-chalcone was developed that can potentially be utilized in treating complex wounds owing to its improved wound healing properties and prevention of potential infections.